Предмет: Математика,
автор: vmosov95
Упростите выражение:sin^2a-cos^2a/sina*cosa
Ответы
Автор ответа:
0
Автор ответа:
0
(sin^2a+cos^2a)/(sina*cosa), если так, то:
(sin^2a+cos^2a)/(sina*cosa)=1/(cos(a)*sin(a))=1/sin(2*a)/2=1/(4*cos(a)*sin(a))=1/2cosec2Если так sin^2a-cos^2a/(sina*cosa), то
sin^2a-cos^2a/(sina*cosa)=-((cos(2*a)-1)/2-(cos(2*a)+1)/2)/(sina*cosa)=-cos(2*a)/(sina*cosa)=-(2*cos(a)^2-1)/(cos(a)*sin(a))=-2*ctg(2*a)
(sin^2a+cos^2a)/(sina*cosa)=1/(cos(a)*sin(a))=1/sin(2*a)/2=1/(4*cos(a)*sin(a))=1/2cosec2Если так sin^2a-cos^2a/(sina*cosa), то
sin^2a-cos^2a/(sina*cosa)=-((cos(2*a)-1)/2-(cos(2*a)+1)/2)/(sina*cosa)=-cos(2*a)/(sina*cosa)=-(2*cos(a)^2-1)/(cos(a)*sin(a))=-2*ctg(2*a)
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Геометрия,
автор: mihaden91
Предмет: Биология,
автор: adileteeember
Предмет: Биология,
автор: Аноним
Предмет: Математика,
автор: mila8410